A questão ambiental em assentamentos da Reforma Agrária : o caso Eduardo Radum no Paraná - Grisa, Sady Domingos Alves (2012)
This research is meant to describe and analyze the process of defining the environmental adequacy in agrarian reform settlements, through which the settlement occurs Eduardo Raduan. The present study aims to measure the impact of environmental adequacy in explorable area of the lots and their relation to economic reproduction of farmers in agrarian reform settlements in Paraná. The specific objectives of monitoring compliance with the environmental standards by the executing agency of Agrarian Reform (INCRA) and beneficiaries of the settlement Eduardo Raduan; assess the environmental variable with regard to the Permanent Preservation Areas (PPAs) and Legal Reserve Areas (ARLs) identifying the discontinuities across the environmental legislation and establish a minimum size of explorable area that enables economic development of these families, with income as an indicator of the minimum monthly wage per lot, considering the economic activity developed in the traditional settlement that is the cattle of milk. Methodologically, was the definition of Brazilian environmental adequacy related to the use and occupation of the land in Areas of Permanent Preservation (APPs) in Areas and Legal Reserves (ARLs), with reference to the national legislation relating to the use and conservation of such areas and to quantify them we used the following parameters: percentage of APPs and ARLs in lots of native vegetation; percentage of annual crops and permanent crops in conflict with these environmental areas.